URGENSI PENDIDIKAN AKHLAK DALAM KURIKULUM PAI MODERN - Ardian Al Hidaya; Nia Ramayanti; Nurhadawiyah Ismayani Hasibuan (Ahsani Taqwim: Jurnal Pendidikan dan Keguruan, 2026)
This research examines the urgency of moral education in the modern Islamic Religious Education (PAI) curriculum amidst the challenges of globalization and rapid technological development. The main problem that becomes the focus of this study is the weakening of moral values and character of students due to foreign cultural influences and the lack of comprehensive implementation of moral education in contemporary PAI learning. This research uses library research method with descriptive qualitative approach. Primary data sources were obtained from books and scientific journals relevant to moral education and PAI curriculum, while secondary data came from articles, previous research results, and educational policy documents. Data analysis was conducted through content analysis techniques with data reduction, data presentation, and conclusion drawing steps. The research results show that moral education has a very high urgency in the modern PAI curriculum as the foundation for forming noble character of students. The integration of moral education in the PAI curriculum has proven effective in forming personalities with noble character, increasing spiritual awareness, and protecting students from negative environmental influences. Holistic implementation of moral education requires collaboration between teachers, parents, and society and is supported by innovative and contextual learning methods in accordance with the times.